(untitled) (Journal of Accounting and Financial Studies ( JAFS ), 2019)
This study aims to expand the traditional model in calculating the break-even point to include the cost of capital invested and the funds employed in industrial companies through a change in the traditional model and the effect of adopting the advanced model of the break point on the operational leverage in planning profits in industrial companies. Where, the analysis of the break-even point and the operational leverage of the tools important by the management, which is used in the field of planning profits. A parity analysis in its sophisticated model will help in planning profits and determine the optimal size of production that maximizes profits. For its part, the operational leverage helps to make decisions regarding the expansion of production and sales in order to maximize profits in large industrial companies. In order to illustrate this, a change has occurred in the traditional model of the tie point on the operational leverage in profit planning. The industrial sector has been chosen for the important role played by this sector in the economy of Kurdistan Region.